Intelligent Distributed Computing V c - Brazier, F. M. T.; Nieuwenhuis, Kees.; Pavlin, Gregor; Warnier, Martijn; Badica, Costin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book represents the combined peer-reviewed proceedings of the Fifth International Symposium on Intelligent Distributed Computing -- IDC 2011 and of the Third International Workshop on Multi-Agent Systems Technology and Semantics -- MASTS 2011. Both events were held in Delft, The Netherlands during October 5-7, 2011. The 33 contributions published in this book address many topics related to theory and applications of intelligent distributed computing and multi-agent systems, including: adaptive and autonomous distributed systems, agent programming, ambient assisted living systems, business process modeling and verification, cloud computing, coalition formation, decision support systems, distributed optimization and constraint satisfaction, gesture recognition, intelligent energy management in WSNs, intelligent logistics, machine learning, mobile agents, parallel and distributed computational intelligence, parallel evolutionary computing, trust metrics and security, scheduling in distributed heterogenous computing environments, semantic Web service composition, social simulation, and software agents for WSNs.
Part I Invited Papers -- Part II Constraints and Optimization -- Part III Parallel and Distributed Computational Intelligence -- Part IV Autonomous and Adaptive Distributed Systems -- Part V Pervasive and Cloud Computing -- Part VI Trust and Security -- Part VII Business Processes -- Part VIII Applications -- Part IX MASTS$1 (B2011.s
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).